Health innovation in cardiovascular diseases - Liew, S.M.; Abdullah, Adina; Abdullah, N.; Chia, Y.C. (Australasian Medical Journal, 2013)
Cardiovascular disease (CVD) remains the leading cause of morbidity and mortality worldwide. Despite efforts to tackle CVD, its prevalence continues to escalate in almost every country. The problem requires an exploration of novel ways to uncover solutions. Health innovations that embrace new knowledge and technology possess the potential to revolutionize the management of CVD. Using findings from published studies on CVD, researchers generated innovations in the areas of global risk assessment, home and remote monitoring and bedside testing. The use of pharmacogenetics and methods to support lifestyle changes represent other potential topics for innovations. Gaps in existing knowledge and practice of CVD provide opportunities for the development of new ideas, practices and technology. However, healthcare professionals need to be cognisant of the limitations of health innovations and advocate for safeguarding patientsâ wellbeing.